2013
DOI: 10.1093/gerona/glt132
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Modifies Ghrelin and Adiponectin Concentrations and Is Related to Inflammation in Older Adults

Abstract: The purpose of this study was to observe exercise training-induced effects on adiponectin, leptin, and ghrelin. Twenty-nine older, healthy participants were classified as physically active (comparison group: N = 15, 70.9 ± 1.2 years) or physically inactive (exercise group: N = 14, 70.5 ± 1.4 years). Exercise group participants completed 12 weeks of combined aerobic and resistance exercise training, whereas comparison group participants maintained their current level of exercise and served as a physically activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 39 publications
6
62
0
Order By: Relevance
“…Adiponectin was found to play an additional role in this setting ( Table 4). We interpret the currently observed increase in endogenous ghrelin levels under ET to be consistent with the alterations observed in studies in older adults18 but consider it to may have additional clinical consequences in the setting of HF. Animal data suggest that endogenous ghrelin plays a crucial role in attenuating pressure overload‐induced cardiac hypertrophy and diastolic dysfunction 21.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Adiponectin was found to play an additional role in this setting ( Table 4). We interpret the currently observed increase in endogenous ghrelin levels under ET to be consistent with the alterations observed in studies in older adults18 but consider it to may have additional clinical consequences in the setting of HF. Animal data suggest that endogenous ghrelin plays a crucial role in attenuating pressure overload‐induced cardiac hypertrophy and diastolic dysfunction 21.…”
Section: Discussionsupporting
confidence: 84%
“…It has been suggested that repeated administration of ghrelin may improve left ventricular function, exercise capacity, and muscle wasting and significantly decrease plasma norepinephrine in patients with HF 17. In older adults, ET was not only related to inflammatory state but also modified ghrelin 18. Thus, the encouraging mechanistic effects of ET on myocardial structural and functional alterations may be attributable to endogenously altered ghrelin and hormonal levels.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, this is the first report of a higher frequency of corticosteroid use among those with the highest sCD14 levels, although levels of membrane-bound CD14 have been reported to increase with corticosteroid use [47]. The observation of fewer individuals in the highest quartile of sCD14 able to walk 3 mph or faster is consistent with prior reports of an association between higher physical activity levels and lower levels of circulating CD14+ cells [48]. That higher sCD14 levels were associated with an increased frequency of self-reported Bfair^or Bpoor^health status is consistent with it being a marker of increased inflammation.…”
Section: Discussionsupporting
confidence: 87%
“…Physically active women also presented a positive association between percentage of body fat and adiponectin, an anti-inflammatory cytokine secreted mainly by adipocytes (28). Although increased body fat attenuates the expression of adiponectin (9), some types of acute physical activity can increase adiponectin levels independently of weight (29)(30)(31)(32), possibly indicating that the anti-inflammatory effect of physical activity overcomes the detrimental effects of excessive fat mass.…”
Section: Discussionmentioning
confidence: 99%